# Question #6daa9

##### 2 Answers

Apr 5, 2016

#### Answer:

#### Explanation:

Take the natural logarithm on both sides

#ln(e^{3x} * e^{2x-1}) = ln(2e)#

From the identity

#ln(ab) = ln(a) + ln(b)#

We can simplify the above equation as

#ln(e^{3x}) + ln(e^{2x-1}) = ln(2) + ln(e)#

#3x + (2x-1) = ln(2) + 1#

#5x = ln(2) + 2#

#x = frac{ln(2) + 2}{5}#

#### Answer:

A slightly different approach

#### Explanation:

Given:

Compare to

Using the above method we have;

Divide both sides by

Take logs of both sides

But